Analisis Komparatif Sensitivitas Metode Mekanistik-Empiris dan Empiris dalam Penentuan Ketebalan Perkerasan Kaku Lalu Lintas Berat - Irvan Efendi; Kurnia Hadi Putra; Ratih Sekartadji; Theresia Maria C.A. (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
This study analyzes the design of rigid pavement thickness on the Dawarblandong road segment using four planning methods: MDPJ 2024, MDPJ 2017, Pd T-14-2003, and AASHTO 1993. Traffic load data and subgrade soil conditions were used to calculate the concrete slab thickness and foundation layers according to each method’s procedure. The results show that the MDPJ 2024 and MDPJ 2017 methods yield concrete slab thicknesses of approximately 305–310 mm using a mechanistic-empirical approach and cumulative traffic load values, while the Pd T-14-2003 and AASHTO 1993 methods produce thinner slabs of 175 mm and 210 mm, respectively, using simpler empirical approaches. These differences indicate that methods incorporating mechanistic analysis of fatigue and erosion damage provide more conservative and safer designs. Reinforcement configuration and slab dimensions are relatively consistent across all methods, though foundation layer thickness and damage control differ. The findings can serve as a reference for selecting concrete pavement design methods that align with traffic conditions and structural safety requirements. Further research is recommended to evaluate field performance and develop integrated design methods.